Pharmaceutical Advertising as a Source of Consumer Self-Empowerment Evidence from Four Countries - Koinig, Isabell; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden (Imprint), 2016)
Isabell Koinig examines how a standardized promotional message for a fictitious over-the-counter (OTC) medication is perceived by consumers in four different countries (Austria, Germany, the U.S., and Brazil), and the degree to which it contributes to their self-empowerment. Building on previous research, informative appeals were expected to not only be most appealing, but also to aid consumers in making qualified and reasonable decisions, educating and "empowering" them by strengthening their beliefs in their own capabilities. A field study on three continents revealed mixed promotional messages to be most effective with regard to both ad evaluation and consumer self-empowerment. Contents Effects of Health Communication and Pharmaceutical Advertising Taking Matters Global: The (Im)Possibilities of Cross-Cultural Advertising Consumer Self-Empowerment: Increasing Consumer Control and Choice Modelling Consumer Self-Empowerment Consumer Responses to Different Advertising Styles Advertising's Contribution to Consumer Self-Empowerment Target Groups Researchers and students in the fields of marketing, media and communications sciences Practitioners in these areas The Author Dr. Isabell Koinig wrote her dissertation under the supervision of Prof. Dr. Sandra Diehl at the Department of Media and Communications at the Alpen-Adria-Universität Klagenfurt, Austria.
Effects of Health Communication and Pharmaceutical Advertising -- Taking Matters Global: The (Im)Possibilities of Cross-Cultural Advertising -- Consumer Self-Empowerment: Increasing Consumer Control and Choice -- Modelling Consumer Self-Empowerment -- Consumer Responses to Different Advertising Styles -- Advertising's Contribution to Consumer Self-Empowerment.
Keywords: Health economics; Globalization; Marketing